Cytokine adsorption as a promising option for septic shock and multiple organ failure due to Candida infection and decompensated type 1 diabetes mellitus. Issue 5 (17th December 2019) - Klinkmann, Gerd; Stope, Matthias B.; Meyer, Andreas
Abstract: Type 1 diabetes mellitus (T1DM) represents one of the most common chronic diseases in childhood. It is associated with high morbidity and mortality rates due to metabolic dysregulation, immunosuppressive effects, and a predisposition to fungal infections. Candidiasis is a severe infection and its prevalence has increased throughout the last decades. We report the case of a 19‐year‐old female patient admitted to our intensive care unit with T1DM and Candida infection associated with severe metabolic acidosis. In the absence of response to high dose catecholamine cardiovascular therapy and the presence of severe metabolic acidosis, a CytoSorb cartridge was implemented into the extracorporeal dialysis circuit resulting in a stabilization of hemodynamics accompanied by a tremendous decrease in vasopressor requirements, control of the hyperinflammatory response, as well as a resolution of metabolic acidosis and regeneration of renal function. Treatment with CytoSorb was safe and feasible without technical problems. Notably, this is the first case description reporting on the effects of CytoSorb in a patient with Candida infection as part of T1DM.